1998
DOI: 10.1002/(sici)1096-8628(19980707)78:3<267::aid-ajmg12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic deletion of chromosome 16p13.3 in patients with Rubinstein-Taybi syndrome

Abstract: The Rubinstein-Taybi syndrome (RTS) is a well-defined entity characterized by growth and mental retardation, broad thumbs and halluces, and typical face. The RTS locus was assigned to 16p13.3, and interstitial submicroscopic deletions of this region (RT1 cosmid, D16S237) were initially identified in 25% of RTS patients. The gene for the human CREB binding protein, the transcriptional coactivator CBP, is included in the RT1 cosmid, and mutations in CBP have recently been identified in nondeleted RTS patients. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…By pooling data from this series and previous studies the cumulative frequency of the 16p13.3 microdeletions is 11% (24 of 219). 1,[3][4][5][6][7] Most previous FISH studies of RTS used only one probe (RT1). 1,3,4,6,7 Our use of different CBP probes in this study did not increase the frequency of detected deletions because all deletions found included RT100 which is very similar to RT1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By pooling data from this series and previous studies the cumulative frequency of the 16p13.3 microdeletions is 11% (24 of 219). 1,[3][4][5][6][7] Most previous FISH studies of RTS used only one probe (RT1). 1,3,4,6,7 Our use of different CBP probes in this study did not increase the frequency of detected deletions because all deletions found included RT100 which is very similar to RT1.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6][7] Most previous FISH studies of RTS used only one probe (RT1). 1,3,4,6,7 Our use of different CBP probes in this study did not increase the frequency of detected deletions because all deletions found included RT100 which is very similar to RT1. 12 For future FISH studies we would recommend using several cosmids for the CBP gene, eg RT100 (exons 14-31), RT191 (exons 3-13) and possibly 420F6 (exon 2) or 304A10 (exon 1), as well as a panel of closely flanking probes (preferably cosmids) to enable the detection of partial deletions of the gene and accurately determine the extent of the A previous study demonstrated by flanking markers that all six deletions were located between cosmid 26 (PKD1/D16S125, telomeric) and cosmid N2 (D16S138, centromeric).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations